The Problem of Confiscation of Non-Relevant Assets in Criminal Processes: A Study of Human Rights Discourse - Hor Agusmen Girsang; Mompang L Panggabean; Rospita A Siregar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Law enforcement is fundamentally the process of transforming legal norms into functional guidelines for conduct within both societal and state frameworks. Its primary objective is to uphold justice and public order by engaging all legal subjects to ensure strict compliance with established regulations. According to Soerjono Soekanto, the essence of law enforcement lies in the harmonization of values articulated through stable principles, which are then manifested in decisive actions. This process serves as the final stage of value interpretation, aimed at establishing, nurturing, and safeguarding communal harmony. Consequently, law enforcement can be understood as the tangible realization of the law itself, ensuring its effectiveness in the pursuit of genuine justice. In the realm of criminal law enforcement, seizure serves as a legitimate coercive measure intended for evidentiary purposes or the recovery of state losses. Nevertheless, the boundary between legal enforcement and the infringement of property rights often becomes ambiguous when investigators confiscate assets that lack a direct nexus to the alleged offense (non-relevant assets). This phenomenon has sparked intense debate from a Human Rights perspective, particularly concerning the constitutional safeguards for private property rights.